The Curriculum Of Standardized Arabic Foreign Language Learning At The Language Center Of Islamic State Universities In Indonesia/ منهج تعليم اللغة الأجنبية العربية القائمة في وحدة مركز اللغة بالجامعات الإسلامية الحكومية إندونيسيا - Noor, Fatwiah; Deviana, Ade Destri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The university has a language center (UPB/PPB) that develops the foreign language skills of students, lecturers, and workers. It has many programs and the curriculum. This research aims to describe the curriculum of standardized Arabic foreign language learning in Language centers at state Islamic universities in Indonesia based on a communicative approach and a standardized test of Foreign Language. This research is qualitative field research with subject purposive, namely universities that fit the scope of this research; its four Universities are Maulana Malik Ibrahim Malang State Islamic University, Sunan Kalijaga Yogyakarta State Islamic University, Syarif Hidayatullah Jakarta State Islamic University, and Sumatra Utara State Islamic University. The data are the curriculum, communicative approach, and standardized Arabic language tests for TOAFL. Analyze data by reducing, presenting, and concluding. The result is that the Language Center of the State Islamic University in Indonesia indicates a curriculum based on centralized and decentralized. It has focused on implementing the TOAFL as a standard Arabic language test by the systems and regulations of each university. In learning Arabic, the implementation of approaches refers to systems language center that is by this communicative approach, including all one system, student-centered learning, and behavioral Approach, also the implementation of variant methods including eclectic method, direct method, active learning, brain-based learning, problem-solving, discussions, conversation, and presentation.